Adsorption, Modeling, Thermodynamic, and Kinetic Studies of Methyl Red Removal from Textile-Polluted Water Using Natural and Purified Organic Matter Rich Clays as Low-Cost Adsorbent. (6th May 2020) - Romdhane, Dalila Fkih; Satlaoui, Yosra; Nasraoui, Rawya; Charef, Abdelkrim; Azouzi, Rim
Abstract : Clay minerals have large surface areas that contribute to their high adsorption capacity. Pure clays were often used. However, their prices remain expensive. However, the natural clay minerals that are locally available can have economic and environmental benefits for textile wastewater treatment. The tested natural clays had given low removal yields. Therefore, we wanted to test particular rich organic matter clay for adsorbing azo dye, which is a very toxic molecule. In order to make the use of this clay type have a better efficiency for removal of this dye from the polluted waters, the optimal conditions had been specified. The results indicated that advised conditions were as follows: 5 min was the contact time of dye-clay; the better adsorbent masses were 0.25 g and 0.5 g per 100 ml solution for raw (ANb) and purified clays (ANp), respectively; the initial dye concentrations were 1 gL −1 for raw clay and 50 mgL −1 for purified clay; pH solution had any effect on the yield of dye removal only when raw clay was used; however, acid environment was advised when purified clay was the adsorbent and for the two tested clays about 20–30°C was the better solution temperature. X-Ray diffraction, Fourier transform infrared (FTIR) spectroscopy, and scanning electron microscopy (SEM) analysis confirmed that functional groups of clay adsorbed the dye. Langmuir maximum adsorption capacities of ANb and ANp were found to be 397 mgg −1 and 132.3 mgg −1 at pH 7 and 5, respectively. Raw and chemically activated samples gave similar results. Adsorption of ANb and ANp data showed better agreement with the pseudo-second-order kinetic model. Thermodynamic parameters of the two adsorbents confirmed that the adsorption was endothermic (ΔH > 0) and spontaneous (ΔG0  < 0). Energy level was high when purified clay was used; however, it was significantly lower when the adsorbent was raw clay. Therefore, it was likely that adsorption by carbonates and organic matter involved small energy amounts. Comparing between these and other previous results, Jebel Louka natural clay type is better recommended for MR removal from textile wastewater, since the removal yield was about 98%. Hence, this tested clay type could provide an alternative low-cost material that could be used in treatment of the textile wastewater rich in MR and the obtained adsorption model and desorption tests provided a background for pilot and industrial scale applications.